INCUBATOR MANAGEMENT MODEL IN INDONESIA - Ajie, Firman Tri; Cahyadi, Eko Ruddy (Jurnal Aplikasi Manajemen, 2017)
Incubator is required to increase the creation of newly technology based firms (NTBFs) that will be dealing with the change of response of market demand as well as technological developments. Incubator management needs sufficient capacity supported by a variety of factors that can determine as the influential factor of an incubator management. The purpose of this study was to compare self-assessment performance based on the factor of incubator management and to describe the diversity of these factors and reduce thus gaining a dominant factor by using principal component analysis, this study was conducted in LIPI, Bandung Techno Park and Solo Techno Park. Purposive sampling was used for the sampling technique with a total population of respondent 18 of 49. Based on the results of research conducted in three incubator institution. LIPI has strength in service criteria compared with two other incubator but weak in objective & management and strategy criteria. Bandung Techno Park has strength in objective & management, strategy, resources criteria. The research has managed to reduce 58 to 13 are considered to be contributing factors in incubator management. This research also generated cumulative proportion diversity of Resources=75.635%; Services=59.177%; Selection System= 69.277%; Strategy=81.584%; Objectives and Management=84.582%. This indicates that each of these factors in the perception of respondents in this study can affect the influential factor in the management of incubators